Union recognition : hearings before the Committee on Post Office and Civil Service, United States Senate, Eighty-fourth Congress, second session, on S. 3593, a bill to amend section 6 of the Act of August 24, 1912, as amended, with respect to the recognition of organizations of Postal and Federal employees, May 15, 24, and June 14, 1956. (U.S. Govt. Print. Off, 1956)
Considers legislation to provide Federal recognition of postal and Federal employee labor organizations. Includes Army report "Civilian Personnel Regulations E2, Grievance Procedures," Mar., 1956. (p. 191-249)